The Effectiveness of Integrating Quillbot for Paraphrasing in Writing Instruction - Thohir, Lalu; Udin, Udin; Isnaeni, Mh; Putera, Lalu Jaswadi (JOLLT Journal of Languages and Language Teaching, 2024)
QuillBot is one of the online programs that can be utilized to enhance studentsâ€™ writing skills. By integrating the paraphrasing tool QuillBot into the writing instruction, this study aimed to examine the effectiveness of QuillBot paraphraser on the studentsâ€™ paraphrasing ability. Additionally, this study sought to find out the students’ opinions on paraphrasing and on the use of QuillBot in paraphrasing. Adopting a mixed method with explanatory design, this study employed quasi-experimental research with a one group pretest posttest design. There were 44 fourth-semester students taking the Academic Writing course in the English study program at the University of Mataram participating in this study. The studentsâ€™ paraphrasing ability was tested before and after the treatment with both manual paraphrasing instruction and QuillBot paraphrasing tool. While, the studentsâ€™ opinions towards paraphrasing instruction integrating the QuillBot paraphrasing tool was discovered through questionnaire. Further, the collected data were analyzed quantitatively and qualitatively to answer the predetermined research objectives. The results of t-test showed that there was a significant difference between the studentsâ€™ paraphrasing ability before and after the treatment with significance value 0.000 lower than 0.05. In addition, most students responded positively to the integration of QuillBot in paraphrasing instruction, as it not only improved their literacy skills but also their motivation in learning paraphrasing in which the use of QuillBot paraphraser is simple, easy, instant and time-saving. This study highlights and confirms the potential of AI tools like QuillBot to enhance language instruction. Other reseachers might compare the efficacy of QuillBot paraphraser to other automatic paraphraser in writing instruction and use both questionnaire and interview to obtain more detailed information about the studentsâ€™ attitudes or opinions.